Cover Feature: Surfactant‐Free and Microporous AlOOH/Al2O3 Nanosheets on TiO2‐Based Nanofibers: A Sustained‐Release Dominated Topotactic Transformation (ChemNanoMat 8/2022). Issue 8 (26th July 2022) - Fu, Wanlin; Zhan, Qi; Yu, Ying; Meng, Xiangyu; Tang, Mingyu; Wang, Yunpeng; Sun, Yueming; Dai, Yunqian
Abstract : TiO2‐based nanofibers decorated with ultrathin and microporous AlOOH/Al2 O3 nanosheets showed high dye capture efficiency and photodegradation capability, furthering green chemistry and low‐carbon economy goals. More information can be found in the Research Article by Yunqian Dai et al.